Improving Self Efficacy and Learning Motivation Through Hybrid Learning Based Google Classroom - Ari Kurniawati; Pardjono Pardjono; Farid Mutohhari; Soffan Nurhaji; Sigit Purnomo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Online learning that is currently taking place causes problems because of the limited learning models that can be done online, so that it can reduce students' self-efficacy and motivation to learn. Learning with the help of Google Classroom is one solution that can be applied to online learning activities in order to increase self-efficacy and student learning motivation. This study aims to analyses the effect of the application of Google Classroom on increasing self-efficacy and student motivation in the Department of Electrical Power Installation Engineering (TITL). This research is a quasi-experimental study using a pretest-posttest design in the control class and the experimental class. The sample in this study amounted to 80 students from the Department of Electrical Power Installation Engineering. The observation method was used to collect data on self-efficacy and learning motivation during the pretest and posttest by using an instrument that was arranged based on indicators on the dependent variable. The data obtained were then tested for prerequisites and then the data were analyzed using paired sample t-test and independent sample t-test. The results of data analysis showed that the use of Google Classroom proved significant in increasing students' self-efficacy and learning motivation in online learning activities for students of the Electrical Engineering Department. Learning activities with the help of Google Classroom are significantly superior to learning activities without the help of Google Classroom.